Sex differences in stress-induced social withdrawal: role of brain derived neurotrophic factor in the bed nucleus of the stria terminalis - Greenberg, Gian D.; Laman-Maharg, Abigail; Campi, Katharine L.; Voigt, Heather; Orr, Veronica N.; Schaal, Leslie; Trainor, Brian C. (Frontiers in Behavioral Neuroscience, 2014)
Depression and anxiety disorders are more common in women than men, and little is known about the neurobiological mechanisms that contribute to this disparity. Recent data suggest that stress-induced changes in neurotrophins have opposing effects on behavior by acting in different brain networks. Social defeat has been an important approach for understanding neurotrophin action, but low female aggression levels in rats and mice have limited the application of these methods primarily to males. We examined the effects of social defeat in monogamous California mice (Peromyscus californicus), a species in which both males and females defend territories. We demonstrate that defeat stress increases mature brain-derived neurotrophic factor (BDNF) protein but not mRNA in the bed nucleus of the stria terminalis (BNST) in females but not males. Changes in BDNF protein were limited to anterior subregions of the BNST, and there were no changes in the adjacent nucleus accumbens (NAc). The effects of defeat on social withdrawal behavior and BDNF were reversed by chronic, low doses of the antidepressant sertraline. However, higher doses of sertraline restored social withdrawal and elevated BDNF levels. Acute treatment with a low dose of sertraline failed to reverse the effects of defeat. Infusions of the selective tyrosine-related kinase B receptor (TrkB) antagonist ANA-12 into the anterior BNST specifically increased social interaction in stressed females but had no effect on behavior in females naïve to defeat. These results suggest that stress-induced increases in BDNF in the anterior BNST contribute to the exaggerated social withdrawal phenotype observed in females.